The BC Community Pharmacy Asthma Study: A Study of Clinical, Economic and Holistic Outcomes Influenced by an Asthma Care Protocol Provided by Specially Trained Community Pharmacists in British Columbia - William Mclean; Jane Gillis; Ron Waller (Canadian Respiratory Journal)
OBJECTIVES: Despite advances in recent years, asthma morbidity and mortality have been noted to be on the increase in the past decade. The present study examined the failures and recommendations of past studies and introduced a new milieu for asthma care - the community pharmacy. The study incorporated a care protocol with the important ingredients of asthma education on medications, triggers, self-monitoring and an asthma plan, with pharmacists taking responsibility for outcomes, assessment of a patient's readiness to change and tailoring education to that readiness, compliance monitoring and physician consultation to achieve asthma prescribing guidelines.